As cepas RH e ME-49 de Toxoplasma gondii induzem a formação de corpos lipídicos em linhagens de macrófagos murinos e fibroblastos - Oliveira, Mário Cézar de (2014)
Lipid droplets (LDs) are active organelles linked to biological functions, in addition to being important sites for lipid mediators storage. Adipocyte differentiation-related protein (ADRP) is known to be a lipid droplet-associating protein, and was originally found in the early stages of adipocyte differentiation and is expressed in a variety of tissues and cells. This work aimed to investigate the relationship of LDs formation and Toxoplasma gondii, type I and type II infection of hematopoietic (RAW 264.7 and J774.1) and non-hematopoietic (NIH/3T3) cells. For this purpose, RAW 264.7 and J774.1 macrophages and NIH/3T3 fibroblasts were infected with strains of T. gondii and LDs formation was analyzed by oil red staining and ADRP expression by immunocitochemistry. It was observed that both macrophages and fibroblast presented LDs formation constitutively, and IFN-γ stimulus increased LDs formation in all cell lines, however, higher LD levels were found in stimulated J774.1 macrophages. Infection with T. gondii increased the LDs formation in both cell lines compared with uninfected cells and ME-49 strain was able to induce higher LDs formation in J774.1 and NIH/3T3 cells compared with RH strain. In parallel, NIH/3T3 presented higher parasitism compared with the other cell lines studied. Lipid droplets inhibition by aspirin (ASA) increased parasitism in macrophages (RAW 264.7 and J774.1) compared with fibroblasts (NIH/3T3). Additionally, cells infected with ME-49 strain presented higher levels of ADRP expression compared with cells infected with RH strain of T. gondii. The results obtained here suggest that the LDs formation contribute to lipid membrane of T. gondii and therefore parasite multiplication in fibroblasts, however, in macrophages the LDs seems to be involved in the control of T. gondii proliferation.